2019
DOI: 10.1016/j.jbiotec.2019.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive prenatal testing as a valuable source of population specific allelic frequencies

Abstract: We declare potential competing financial interest in the form of employee contracts (see affiliations for each author) with Geneton Ltd. that participated in the development of a commercial NIPT test in Slovakia. On the other hand, Geneton Ltd. is not a provider of this commercial test, but still continues to do basic and applied research in the field of NIPT.Minarik G and Sekelska M are employees of Medirex Inc./TrisomyTest Ltd. (the commercial providers of NIPT testing in Slovakia), their participation in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Although the 112 sequencing depth per sample was low, there might be more than one read from the same 113 sample overlapping at a genome position. This problem may affect the estimation of allele 114 frequency because the estimation is based on the assumption that a sample may contribute 115 only 0 or 1 allele (read) at any given genome position [12,13]. For instance, we found that the 116 average percentage of genome positions with depth 2x (i.e.…”
Section: Genome Coverage and Sequencing Depth Of The Nipt Dataset 100mentioning
confidence: 99%
See 4 more Smart Citations
“…Although the 112 sequencing depth per sample was low, there might be more than one read from the same 113 sample overlapping at a genome position. This problem may affect the estimation of allele 114 frequency because the estimation is based on the assumption that a sample may contribute 115 only 0 or 1 allele (read) at any given genome position [12,13]. For instance, we found that the 116 average percentage of genome positions with depth 2x (i.e.…”
Section: Genome Coverage and Sequencing Depth Of The Nipt Dataset 100mentioning
confidence: 99%
“…At any genome position, there were on average 47 out of 119 2,683 samples that each contributed two reads (Supplementary Figure S3). To address this 120 problem, we followed a filtering strategy from previous studies [12,13] to keep only one read if 121 there were overlapping reads in a sample. Thus, for every genome position, each sample could 122…”
Section: Genome Coverage and Sequencing Depth Of The Nipt Dataset 100mentioning
confidence: 99%
See 3 more Smart Citations